2006
DOI: 10.1016/j.seppur.2006.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mechanisms of phosphate adsorption on dewatered alum sludge

Abstract: The adsorption characteristics of phosphate adsorption on the dewatered alum sludge were identified as a function of pH and ion strengths in solution. In addition, adsorption mechanisms were investigated by conducting batch tests on both the hydrolysis and P-adsorption process of the alum sludge, and making a comparative analysis to gain newer insights into understanding the adsorption process. Results show that the adsorption capacity decreased from 3.5 to 0.7 mg-P/g-sludge when the solution pH was increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(189 citation statements)
references
References 21 publications
9
153
0
4
Order By: Relevance
“…This was a sign of the desorption/release of OM organic matters from the alum sludge as a result of the competitive adsorption between phosphate and humic substances for adsorption site on the surface of alum sludge. This has been previously investigated and reported (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This was a sign of the desorption/release of OM organic matters from the alum sludge as a result of the competitive adsorption between phosphate and humic substances for adsorption site on the surface of alum sludge. This has been previously investigated and reported (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The huge increase in P concentration in the used Al-WTR attests to the high P 303 adsorption capacity of the Al-WTR. In our previous studies, it was shown that Al-WTR has a 304 preferential adsorption for P (Yang et al 2006) and the adsorption capacity of the Al-WTR can 305 range from 10.2 mg-P/g to 31.9 mg-P/g (determined using the Langmuir adsorption isotherm) 306 (Babatunde, 2007). 307…”
mentioning
confidence: 99%
“…This is unusual in conventional CWs as initial P removal is generally poor due to the poor P adsorption capacity of the gravel or other media used, and the fact that the other P removal mechanisms, such as biomass and plant uptake may take several months before they can significantly contribute to P removal. However, the dewatered alum sludge cake used herein is mainly composed of aluminium ions and this facilitates its ability to enhance P removal from wastewater through ligand exchange (Yang et al, 2006). Interestingly, the mean level of dissolved aluminium (Al) monitored in the effluent from the system was 0.04  0.01 mg/l and this is well below the discharge limit of 0.2 mg/l for Al discharge into all waters.…”
Section: Overall Treatment Performancementioning
confidence: 99%